The brown adipose tissue glucagon receptor is functional but not essential for control of energy homeostasis in mice - Beaudry, Jacqueline L. (Mol Metab, 2019)
OBJECTIVE: Administration of glucagon (GCG) or GCG-containing co-agonists reduces body weight and increases energy expenditure. These actions appear to be transduced by multiple direct and indirect GCG receptor (GCGR)-dependent mechanisms. Although the canonical GCGR is expressed in brown adipose tissue (BAT) the importance of BAT GCGR activity for the physiological control of body weight, or the response to GCG agonism, has not been defined. METHODS: We studied the mechanisms linking GCG action to acute increases in oxygen consumption using wildtype (WT), Ucp1(−/−) and Fgf21(−/−) mice. The importance of basal GCGR expression within the Myf5(+) domain for control of body weight, adiposity, glucose and lipid metabolism, food intake, and energy expenditure was examined in Gcgr(BAT−/−) mice housed at room temperature or 4 °C, fed a regular chow diet (RCD) or after a prolonged exposure to high fat diet (HFD). RESULTS: Acute GCG administration induced lipolysis and increased the expression of thermogenic genes in BAT cells, whereas knockdown of Gcgr reduced expression of genes related to thermogenesis. GCG increased energy expenditure (measured by oxygen consumption) both in vivo in WT mice and ex vivo in BAT and liver explants. GCG also increased acute energy expenditure in Ucp1(−/−) mice, but these actions were partially blunted in Ffg21(−/−) mice. However, acute GCG administration also robustly increased oxygen consumption in Gcgr(BAT−/−) mice. Moreover, body weight, glycemia, lipid metabolism, body temperature, food intake, activity, energy expenditure and adipose tissue gene expression profiles were normal in Gcgr(BAT−/−) mice, either on RCD or HFD, whether studied at room temperature, or chronically housed at 4 °C. CONCLUSIONS: Exogenous GCG increases oxygen consumption in mice, also evident both in liver and BAT explants ex vivo, through UCP1-independent, FGF21-dependent pathways. Nevertheless, GCGR signaling within BAT is not physiologically essential for control of body weight, whole body energy expenditure, glucose homeostasis, or the adaptive metabolic response to cold or prolonged exposure to an energy dense diet.